Regulation of the carotenoid biosynthetic pathway in the green microalga Dunaliella salina and the diatom Phaeodactylum tricornutum - Coesel, Sacha (2011)
Tese dout. , Faculdade de Ciências do Mar e do Ambiente, 2007, Universidade do Algarve